Travel style is a major risk factor for diarrhoea in India: a prospective cohort study. (July 2015) - Schindler, V.M.; Jaeger, V.K.; Held, L.; Hatz, C.; Bühler, S.
Abstract: Although some studies suggested specific foods/beverages as risk factors for travellers' diarrhoea (TD), details of transmission remain unclear. We assessed the influence of travel style (luxury/middle-class versus backpacking) on TD risk. TD attack rates were compared in a prospective study among travellers to India at the University of Zurich's Travel Clinic. Information on consumption of foods/beverages was collected. Seventy-one luxury/middle-class travellers and 21 backpackers completed the study; overall 37% suffered from TD (62% backpackers, 30% luxury/middle-class travellers, OR 4.43, p 0.022). Travel style rather than the consumption of specific foods/beverages appears to be a risk factor for TD development.